KEMAMPUAN MENULIS PUISI SISWA KELAS X SMA N 1 KECAMATAN BASA AMPEK BALAI KABUPATEN PESISIR SELATAN DENGAN MENGGUNAKAN STRATEGI MIND MAPPING - Putri, Dwi Eka; Gusnetti, Gusnetti; Hartati, Yulia Sri (Pendidikan Bahasa Indonesia, 2014)
The background of this research is less attention of students to use verse, rhythm, and tones in writing poetry and also teacher doesnât use variation strategy. The purpose of this research is to describe students ability in writing the poetry in class X at SMA N 1 Kecamatan Basa Ampek Balai Kabupaten Pesisir Selatan By using mind mapping strategy. This research is quantitative research which is using descriptive method the population of this research is the students of class X at SMAN 1 Kecamatan Basa Ampek Balai Kabupaten Pesisir Selatan which have total 283 students. The sample is collected by simple random sampling technique, so the class X5 is as the sample. The instrument which is used is the test, then getting the data to be analizeÂ based on data analysis, it shows the conclusion that the ability of class X SMA N 1 Kecamatan Basa Ampek Balai Kabupaten Pesisir Selatan in writing the poetry is good by using mind mapping strategy (averages in 76-85%).